Legion. The complete season two. [videorecording (DVD)] - Stevens, Dan, 1982-; Keller, Rachel, 1991-; Plaza, Aubrey, 1984-; Claremont, Chris, 1950- (FX Productions, 2018)
Legion follows the story of David Haller, a man who believed he was schizophrenic but discovered he might be the most powerful mutant in the world. With help from a team of specialists, David harnessed his unique abilities and learned he had been haunted by a malicious parasite. Now, David is all that stands in the way of Amahl Farouk from attaining infinite and world-ending power.